The Triad of Social, Political and Religious Discourse in the Novel: The Novels of Sotingeh, Meryema Kiçe Jinek ji Zemanek dî and Tavge as Examples - Waisi, Nechirvan; Omar, Ameen (Humanities Journal of University of Zakho, 2021)
The present study is an attempt to undertake discourse analysis for three novels written in the Bahdinan area of Iraqi Kurdistan: Sotingeh (Crematory) by Bilind Muhammad; Meryema Kiçe Jinek ji Zemanek dî (Mariama, a Woman from Another Time) by Sabri Silevani; and Tavge (Tavgah) by Tahseen Navishki. The study has been conducted within the framework of discourse analysis in literary criticism, but in a descriptive way. We have attempted to analyze the themes of incidents in the study‌s samples in order to uncover the main discourse of each novelist. The hypothesis question to which the study tries to find an answer is whether the novelists are able to write frankly about the triad of society, politics and religion, and to what extent do they have a common perspective in this regard. The study is divided into two main parts; the first part discusses the concepts of discourse and discourse analysis. The second part is devoted to the analysis of the discourses in the study‌s samples, in terms of the social, political and religious discourses reflected in the novels. The study demonstrates that both Silevani and Navishki criticize their society and the reality in which they live in their discourses. However, Muhammad‌s discourse in his novel is more a historical and political one. Keywords: Novel, discourse, discourse analysis, the triad of society, politics and religion